Development and application of ultrafiltration and reverse osmosis membranes - Malherbe, Gideon Francois (Cape Technikon, 2013)
Thesis (Masters Diploma (Technology)--Cape Technikon, Cape Town,1993 === Various experimental and established membranes were tested on industrial effluents. Ultrafiltration, reverse osmosis and nanofiltration membranes were used in various applications. Research was done on aspects such as the cleaning of fouled membranes, production quality control and process development. Polyvinyl alcohol ultra-thin-film reverse osmosis membranes were manufactured for the desalination of brackish water to a potable standard. The membranes were manufactured in the tubular configuration. Experimental ultrafiltration, reverse osmosis and nanofiltration membranes were tested on cooling water blowdown on a laboratory-scale. On-site testing was done directly on the effluent at a later stage. A s!udy was also conducted to determine the effect of gel-polarization on membrane performance. The gel-layer model was used to predict the limiting flux of specific membranes. Membrane processes were also applied in the fractionation of wine-lees to provide usable by-products such as yeast cells and potassium bitartrate. Ultrafiltration membranes operated in diafiltration mode were used to "wash" the slurry at different solid concentrations. The bitartrate-rich permeate collected from ultrafiltration was then concentrated using reverse osmosis and nanofiltration to allow subsequent precipitation of the product.